Empowering Early Childhood EFL Teachers: A Service-Learning Model for TEYL Professional Development in Indonesia - Khoiriyah Khoiriyah; Estu Widodo (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
TEYL in pre-primary education has received increasing attention for its contributions to children’s early language development, cognitive growth, and future global communication skills. In the Indonesian EFL context, however, implementation remains limited by teachers’ insufficient English proficiency, lack of pedagogical training, low confidence, and minimal access to structured materials and exposure. This community service program employed a service-learning approach, defined as applying knowledge and expertise through active engagement with the community. In this context, the community service program is objected to address the teachers’ challenges in teaching English to very young learners as well as enhancing their teaching competence. The framework followed four sequential stages including concentrated experience, reflective observation, abstract conceptualization, and active experimentation. Overall, the program was designed carefully based on the need analysis, and successfully enrich the teachers’ competence. This result of the survey also consistently indicate that teachers perceived the professional development workshop as highly effective in enhancing their understanding and readiness to apply the knowledge into their day-to-day teaching practice. Hence, this community service was expected to enhance the teachers’ competence especially in teaching English to very young learners.